Dupchanchia Model of Students’ drop-out control through engagement and appreciation after Covid-19: A Behavioral Policy intervention in the field administration of Bangladesh - Zihady, Shumon (Technium Social Sciences Journal, 2023)
Bangladesh is a country which has successfully accomplished the millennium development goals. Upon such accomplishment and with new growing consensus with the global community, the country at present is in pursuit of achieving the sustainable development goals with mostly concentrating on the education sector. However, what impacted the growth and pace of the initiatives was the overwhelming impact of Covid-19 and the lockdown afterwards. Academic institutions remained closed at least for two years which resulted in a compromising number of students after the resumption. This study starts from the identification of a genuine problem with original field level data of the gradually declining number of students. It requires policy intervention centrally and locally. As a crucial part of local government, I have been working as the chief executive officer of a sub-district called Dupchanchia, and coordinating government departments to implement government policy. After rigorous discussion and brainstorming among the local stakeholders and teachers we uncovered that the students have become demotivated, traumatized and panicked of social engagement and any form of shared activities like classes, games and others. It required us to find out a local policy solution followed by a detailed literature review and primary data collection maneuver. Taking twenty schools into consideration for the study, the project initiated a behavioral policy intervention in ten particular schools and did not interfere with the other ten schools. I engaged local teachers, students and other related stakeholders and continued to use six behavioral tools to change the choice structure of the students of ten selected schools. We observed other ten schools without intervening in their environment and academic atmosphere at all. At the end of the study we collected data through key informant interviews and focus group discussion engaging teachers, peoples’ representatives and government officials. Behavioral public policy intervention like nudge and engagement approaches are found to have a positive relation with the change in students number and their performance in the academic and co-curricular activities. This approach may contribute to controlling students’ drop out in the lower and lower middle income countries after Covid shock. This policy intervention may have some challenges and limitations which need intensive and rigorous pre-study and prolonged design. Nevertheless, it has unlimited opportunities to be addressed.